Exploring the Role of Knowledge Management in the Link Between Organizational Culture and Financial Performance: Evidence from Libyan Higher Education Institutions - Aghel, Mohamed; Azam, S. M. Ferdous (International Review of Management and Marketing, 2025)
This study investigates the relationship between organizational culture and financial performance in Libyan higher education institutions, with a specific focus on the mediating role of knowledge management and the moderating effect of professional experience. Using a quantitative approach, data were collected from 347 financial stakeholders, including accountants, auditors, and finance managers, and analyzed through Structural Equation Modeling (SEM). The findings reveal that knowledge management significantly mediates the link between organizational culture and financial performance, while years of experience enhance knowledge management’s contribution to financial outcomes but do not directly affect the relationship between organizational culture and financial performance. By highlighting the critical role of a knowledge-driven culture and the value of experienced staff, this study contributes new insights to the higher education finance literature in a post-conflict developing context and provides practical implications for policymakers and university leaders aiming to strengthen financial performance through strategic cultural and knowledge management initiatives.